Vegetation structure of Sumatran Orangutan (Pongo abelii) habitat in North Sumatra, Indonesia - Anita Zaitunah; SAMSURI; Satia Ras (Society for Indonesian Biodiversity, 2021)
Abstract. Zaitunah A, Samsuri, Ras S. 2021. Vegetation structure of Sumatran Orangutan (Pongo abelii) habitat in North Sumatra, Indonesia. Biodiversitas 22: 635-641. Gunung Leuser National Park forest in the Bukit Lawang section is the habitat of Sumatran Orangutan (Pongo abelii). There have been reports of the orangutans visiting the village. As some tree species are required for their sustenance to provide nests and food, there is a need to study species diversity availability in their habitat. Thus, the aim of the research was to analyze the composition and structure of the area's vegetation-this was done for the forestand mixed plantation. The sampling for the measurement of tree parameters was conducted using the line strip method. The strips (width 50 m, length 250 m) were constituted by a sub-plot measuring for seedling, pole, sapling, and trees. Within the sampling area, 181 species were found. Species within Dipterocarpaceae showed higher important value index (IVI) compared to other species in all layers. Shorea parviflora and Shorea ovalis were among the species with higher IVI in all the layers. The presence of species of Dipterocarpaceae and other species preferred by orangutans will support their quality of life. Therefore, orangutans prefer staying in the forest to entering the garden. Thus, it is concluded that their entry into the mixed gardens is related to the garden's proximity to the forest. Conservation efforts are needed to minimize the conflict between man and orangutan in the surrounding area.